2021
DOI: 10.3390/metabo11010028
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Reprogramming of Cancer Cells during Tumor Progression and Metastasis

Abstract: Cancer cells face various metabolic challenges during tumor progression, including growth in the nutrient-altered and oxygen-deficient microenvironment of the primary site, intravasation into vessels where anchorage-independent growth is required, and colonization of distant organs where the environment is distinct from that of the primary site. Thus, cancer cells must reprogram their metabolic state in every step of cancer progression. Metabolic reprogramming is now recognized as a hallmark of cancer cells an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
71
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(82 citation statements)
references
References 173 publications
(176 reference statements)
0
71
0
Order By: Relevance
“…Because pre-malignant and cancer cells must reprogram their metabolic state in every step of progression to survive in nutrient-altered conditions, metabolic reprogramming is recognized as a cancer hallmark [58]. Defining how cancer cells rewire metabolism towards proliferation, which our understanding of has progressed rapidly, opens new therapeutic intervention strategies [25][26][27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…Because pre-malignant and cancer cells must reprogram their metabolic state in every step of progression to survive in nutrient-altered conditions, metabolic reprogramming is recognized as a cancer hallmark [58]. Defining how cancer cells rewire metabolism towards proliferation, which our understanding of has progressed rapidly, opens new therapeutic intervention strategies [25][26][27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that mitophagy plays an important role in the metabolic transition of tumors and the maintenance of phenotype of cancer stem cells (CSCs). Continuous reprogramming of cellular metabolism is a critical milestone event in cancer ( Pavlova and Thompson, 2016 ; Chen et al, 2020 ; Ohshima and Morii, 2021 ). Metabolic alterations lead to enhanced uptake and utilization of glucose and amino acid nutrients from a nutrient-deficient environment and increased use of glycolysis/TCA cycle intermediates for macromolecular biosynthesis.…”
Section: The Role Of Mitophagy In Cancermentioning
confidence: 99%
“…During tumor progression, tumor cells reprogramed their metabolic state from catabolism to anabolism for uncontrolled cell proliferation (15,16). Previous study reported that CDK7 inhibition suppresses human non-small-cell lung cancer cells through interference with cancer metabolism (25).…”
Section: Thz1 Disrupts the Cellular Metabolic Pathways Of B-all Cells In Vitromentioning
confidence: 99%
“…Metabolic reprogramming is a hallmark of tumor cells. The cellular metabolism of tumor cells is reprogrammed to fulfill the excessive metabolic demands for uncontrolled cell proliferation (15,16). Glycolysis, also known as the Warburg effect, is the initial step in glucose metabolism, which consumes a large number of glucose and results in lactate production even under adequate oxygen conditions.…”
Section: Introductionmentioning
confidence: 99%